Modeling the Propagation of Ultrasonic Guided Waves in a Composite Plate by a Spectral Approximation Method - ZITOUNI, Ismaine; RHIMINI, Hassan; CHOUAF, Abdelkerim (Engineering Transactions, 2023)
Graphite-epoxy composites have been able to meet the multiple requirements of the space industry. However, the radiation from the spatial environment and non-perfect adhesion between the fibers and the matrix can lead to the appearance of imperfections. To handle this, we use non-destructive testing by ultrasonic guided waves known for its high accuracy in detecting defects. In this article, we study the propagation of ultrasonic guided waves in a graphite-epoxy composite plate by the spectral method. First, the mathematical formalism is explained for modeling guided waves in the composite material. Next, we plot the dispersion curves of the composite plate in different orientations of the fibers with a MATLAB program and the results are compared with those of the DISPERSE software. These give us information on the modes that propagate in the structure. We elaborate and explain a technique based on displacement symmetry to distinguish between the different modes. A discussion based on time-saving and accuracy is established to show the advantages of the method. The second part of our paper consists in giving a physical meaning to the spectral displacements normalized in amplitude. We propose to normalize the spectral eigenvectors by the acoustic power. We plot the displacement and stress profiles of the guided modes and we compare our results to the analytical ones. Perfect correspondence is found, indicating the accuracy of the approach developed. In addition, a study of the vibrational state in the composite plate is established for Lamb and horizontal shear modes at a specific frequency.